Hagiographic Narrative and its Interpretations - Alexandra S. Balakhovskaya (Studia Litterarum)
The article based on the hagiography of the bishop of Constantinople St. John Chrysostom studies a development process of the hagiographical version of the saint’s biography and its interpretation in the hagiographical tradition. The life of the saint, a literary work created in the context of a church cult, expresses the actual church ideology and is the answer to the current problems of the church life. The Life written by Pseudo-George of Alexandria reflects one of them — the intervention of secular authorities in the affairs of the Church in Byzantium. St. John Chrysostom and Empress Eudoxia are represented here as symbolic figures marking this opposition. On the other hand, they are correlated with the biblical images of the prophet Elijah and Queen Jezebel — their typological prototypes. The Life of Pseudo-George is a literary model that formed the basis of the subsequent hagiographical tradition, part of which are two encomiums, written by St. John of Damascus and Emperor Leo VI the Wise. In these works, we find the interpretation and further development of the theme of contradiction between spiritual and secular powers.